Bacteriophage as an alternative to prevent reptile‐associated Salmonella transmission. (17th January 2021) - Kwon, Jun; Kim, Sang Geun; Kim, Hyoun Joong; Giri, Sib Sankar; Kim, Sang Wha; Lee, Sung Bin; Park, Se Chang
Abstract: Salmonellosis is a major global public health issue; its most common infection, gastroenteritis, accounts for approximately 90 million illnesses and 150, 000 mortalities per year. Eradicating salmonellosis requires surveillance, prevention and treatment, entailing large expenditures. However, it is difficult to control Salmonella transmission because it occurs via multiple routes; exotic reptiles are a reservoir of Salmonella and comprise one such route. As the popularity of exotic pets and animal exhibition has increased, human encounters with reptiles have also increased. As a result, reptile‐associated salmonellosis (RAS) has been recognized as an emerging disease. The development of antimicrobial resistance in RAS‐causing Salmonella sp. requires alternatives to antibiotics. In this study, bacteriophages have been established as an alternative to antibiotics because only target bacteria are lysed; thus, they are promising biocontrol agents. Here, bacteriophage pSal‐SNUABM‐02, which infects and lyses reptile Salmonella isolates, was isolated and characterized. The morphology, host range, growth traits and stability of the phage were investigated. The phage was assigned to Myoviridae and was stable in the following conditions: pH 5–9, 4–37°C, and ultravioletA/ultravioletB (UVA/UVB) exposure. Salmonella clearance efficacy was tested using planktonic cell lysis activity and biofilm degradation on polystyrene 96‐well plates and reptile skin fragments. The phage exhibited vigorous lysis activity against planktonic cells. In in vitro biofilm degradation tests on reptile skin and polystyrene plates, both low‐ and high‐concentration phage treatments lowered bacterial cell viability by approximately 2.5–3 log colony‐forming units and also decreased biomass. Thus, bacteriophages are a promising alternative to antibiotics for the prevention and eradication of RAS.